Distribution of Primary Resistance Mutations in Saint Petersburg in Patients with Chronic Hepatitis C - Diana Valutite; Yulia Ostankova; Alexandr Semenov; Liudmila Lyalina; Areg Totolian (Diagnostics, 2022)
The advent of direct-acting antiviral drugs (DAAs) was a breakthrough in the treatment of patients with chronic hepatitis C, yet high viral replication errors can lead to the development of resistance associated variants (RAVs). Thus, assessment of RAV in infected patients is necessary to monitor treatment effectiveness. The aim of our study was to investigate the presence of primary resistance mutations in the NS3 and NS5 regions of HCV in treatment-naive patients. Samples were taken from 42 patients with HCV who had not previously received DAA treatment. In the present study, we used the method for determining drug resistance mutations based on direct sequencing of the NS3, NS5A, and NS5B genes developed by the Saint Petersburg Pasteur Institute. Primary mutations associated with resistance were detected in 5 patients (12%). According to the Geno2pheno [hcv] 0.92 database, nucleotide substitutions were identified in various viral genes conferring resistance or decreased sensitivity to the respective inhibitors. This study has shown different mutations in the analyzed genes in patients with HCV who had not previously received DAA treatment. These mutations may increase the likelihood of treatment failure in the future.